Effect of Dietary Supplementation of Hydrolyzed Yeast on Growth Performance, Digestibility, Rumen Fermentation, and Hematology in Growing Beef Cattle - Nirawan Gunun; Ittipol Sanjun; Chatchai Kaewpila; Suban Foiklang; Anusorn Cherdthong; Metha Wanapat; Sineenart Polyorach; Waroon Khota; Thachawech Kimprasit; Piyawit Kesorn; Nipa Milintawisamai; Pongsatorn Gunun (My University, 2022)
This experiment was conducted to assess the effect of hydrolyzed yeast (HY) on growth performance, nutrient digestibility, rumen fermentation, and hematology in growing crossbred Bos indicus cattle. Twenty crossbred beef cattle with an initial body weight (BW) of 142 ± 12 kg were randomly assigned to one of four treatments for 90 d in a randomized complete block design (RCBD) having five blocks based on a homogenous subpopulation of sex and BW. Cattle were fed with a total mixed ration (TMR) and supplemented with HY at 0, 1, 2, and 3 g/kg dry matter (DM), respectively. Supplementation with the HY did not change average daily gain (ADG), dry matter intake (DMI), and gain to feed ratio (G:F) (p ≥ 0.06). The addition of HY did not adversely affect nutrient intake (p ≥ 0.48), while the digestibility of crude protein (CP) increased quadratically (p= 0.03) in the cattle receiving HY. The addition of HY did not affect rumen pH, but NH3-N concentration increased linearly (p = 0.02) in the cattle. The total volatile fatty acid (total VFA) increased quadratically (p= 0.03) when cattle were fed with HY supplementation. The proportion of acetate decreased cubically (p= 0.03) while propionate increased cubically (p= 0.01), resulting in a decrease in the acetate to propionate ratio (p= 0.01) when cattle were fed with HY supplementation. In addition, acetate was the lowest, but total VFA and propionate were the highest in cattle fed the HY at 2 g/kg DM. Butyrate increased cubically (p = 0.02) with the addition of HY. The protozoal and fungal populations were similar among treatments (p ≥ 0.11), but the bacterial population increased linearly (p < 0.01) with the addition of HY. Supplementation of HY did not influence blood urea nitrogen (BUN), red blood cells (RBC), hemoglobin, hematocrit, white blood cells (WBC), lymphocytes, or eosinophils (p≥ 0.10). However, monocytes and neutrophils increased linearly (p = 0.04 and p = 0.01, respectively) by HY supplementation. In conclusion, supplementation of HY at 2 g/kg DM promotes CP digestibility, rumen fermentation efficiency, and hematology but does not affect the growth performance of growing beef cattle.
Keywords: Beef Cattle; Isovalerate; Ruminant Nutrition and Digestive Physiology